2004
DOI: 10.1016/s0092-8674(04)00115-1
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control by MAPK Signaling in Long-Term Synaptic Plasticity and Memory

Abstract: Enduring forms of synaptic plasticity and memory require new protein synthesis, but little is known about the underlying regulatory mechanisms. Here, we investigate the role of MAPK signaling in these processes. Conditional expression of a dominant-negative form of MEK1 in the postnatal murine forebrain inhibited ERK activation and caused selective deficits in hippocampal memory retention and the translation-dependent, transcription-independent phase of hippocampal L-LTP. In hippocampal neurons, ERK inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
621
3
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 764 publications
(678 citation statements)
references
References 53 publications
51
621
3
3
Order By: Relevance
“…Therefore, PGS32 presumably was able to prime the ERK/MAP kinase cascade by activating ERK. A large body of research has demonstrated that ERK activation is required for the induction and maintenance of LTP, as well as for hippocampal memory formation and retention [26,27] . The ability of PGS32 to activate ERK therefore provides initial evidence that this saponin can play a role in regulating cognitive function and synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PGS32 presumably was able to prime the ERK/MAP kinase cascade by activating ERK. A large body of research has demonstrated that ERK activation is required for the induction and maintenance of LTP, as well as for hippocampal memory formation and retention [26,27] . The ability of PGS32 to activate ERK therefore provides initial evidence that this saponin can play a role in regulating cognitive function and synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Another ADR, mycalolide B, also blocked the effect of activin on spine length, and the average spine lengths in neurons treated with activin alone versus neurons treated with activin and 50 nM mycalolide B were 1.59±0.054 m versus 1.50±0.049 m, respectively. The MAP kinase pathway is involved in the effects of activin Because MAP kinase signaling modulates dendritic spine morphology (Wu et al, 2001) and LTP maintenance (Kelleher, 3rd et al, 2004;Patterson et al, 2001), we asked whether the MAP kinase pathway also mediates the activin signaling that alters spinal morphology. When hippocampal primary cultures were treated with activin, phosphorylation of ERK1/2 increased by twofold within 0.5-1 hour (Fig.…”
Section: F-actin-destabilizing Reagents Block the Effects Of Activinmentioning
confidence: 99%
“…Kelleher et al (2004) demonstrated that the extracellular signalregulated kinase (ERK)/mitogen-activated protein kinase pathway is involved in regulating the phosphorylation state of numerous factors implicated in controlling translation initiation, including eIF4E, 4E-BP1, and the ribosomal protein S6. The genetically altered mice used in this study also showed deficits in long-term potentiation (LTP) and hippocampus-dependent memory.…”
Section: Introductionmentioning
confidence: 99%